Electromyographic analysis of the traditional and spin throwing techniques for goalball games related to ball velocity for selected upper extremity muscles - Göksen, A.; Ince, G.; Alcan, V. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Background Goalball is a popular sport among visually impaired individuals, offering many physical and social benefits. Evaluating performance in Goalball, particularly understanding factors influencing ball velocity during throwing techniques, is essential for optimizing training programs and enhancing player performance. However, there is limited research on muscle activation patterns during Goalball throwing movements, needing further investigation to address this gap. Therefore, this study aims to examine muscle activity in sub-elite visually impaired Goalball players during different throwing techniques and visual conditions, focusing on its relationship with ball velocity.